2002
DOI: 10.1007/s00232-001-0176-0
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Inactivation of Voltage-dependent K+ Channels in Human B Lymphoma Cells

Abstract: The voltage-dependent K (KV) channel in Daudi human B lymphoma cells was characterized by using patch-clamp techniques. Whole-cell voltage-clamp experiments demonstrated that cell membrane depolarization induced a transient (time-dependent) outward current followed by a steady-state (time-independent) component. The time-dependent current resembled behavior of the type n channel, such as use dependence and a unique blockade by tetraethylammonium (TEA). Both time-dependent and time-independent currents were blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
5
14
0
Order By: Relevance
“…Consistent with our previous report (19), only outward K ϩ currents (but not any inward currents) were recorded as shown by a representative whole-cell recording from a total of 118 experiments (Fig. 1A).…”
Section: Resultssupporting
confidence: 91%
“…Consistent with our previous report (19), only outward K ϩ currents (but not any inward currents) were recorded as shown by a representative whole-cell recording from a total of 118 experiments (Fig. 1A).…”
Section: Resultssupporting
confidence: 91%
“…Among K + channels, voltage-gated K + channel, as later referred to as Kv1.3 channel, was initially reported to affect proliferation of T lymphocyte [9]. We have previously shown that Kv1.3 channel is highly expressed in Daudi cells [41]. However, the present study suggests that an IK channel, instead of Kv1.3, is responsible for Daudi cell cycle progression.…”
Section: Discussionmentioning
confidence: 62%
“…Our previous finding that Kv1.3 channel is highly expressed in malignant Daudi B cells [41] prompted us to hypothesize that this voltage-dependent channel might mediate cell cycle progression of malignant B lymphocyte. Surprisingly, we found that Daudi cell cycle progression is not affected by selective inhibition of Kv1.3 channel with MgTX but inhibited by either nonselective blockage of K + channels with TEA or selective blockage of IK channels with TRAM-34.…”
Section: Tea and Tram-34 But Not Mgtx Inhibits Daudi Cell Cycle Promentioning
confidence: 98%
See 2 more Smart Citations